Taxonomic revision of the genus Poropuntius (Teleostei: Cyprinidae) in Peninsular Malaysia - Muhammad-Rasul, Abdullah Halim; Ramli, Rosli; Low, Van Lun; Ahmad, Amirrudin; Grudpan, Chaiwut; Koolkalya, Sontaya; Khaironizam, Md Zain (Magnolia Press, 2018)
Up to three nominal species of the cyprinid fish genus Poropuntius (i.e. P. deauratus [Valenciennes in Cuvier & Valenciennes 1842], P. normani [Smith 1931], and P. smedleyi [de Beaufort 1933]) have been reported to occur in Peninsular Malaysian freshwater ecosystems. However, low morphological differentiation among species of Poropuntius causes confusion and it is still unknown how many valid species of Poropuntius occur in this region. The goal of this study is to review the taxonomic status of Poropuntius in Peninsular Malaysia by using morphological and molecular characters. Principal Component Analysis (PCA) on a morphometric dataset including 281 specimens of Poropuntius from Peninsular Malaysia and P. normani from Thailand (type locality) failed to identify non-overlapping clusters within sampled specimens. A phylogenetic tree based on cytochrome oxidase subunit I (COI) showed intraspecific levels of genetic differentiation within Poropuntius of Peninsular Malaysia and the specimens of P. normani from Thailand form a monophyletic group. Our results strongly support the presence of only one species of Poropuntius in Peninsular Malaysia, P. normani. We demonstrate that P. smedleyi described from Johor, southern Peninsular Malaysia, is a junior synonym of P. normani. The previous reports of the presence of P. deauratus in Peninsular Malaysia are doubtful because this species was described from Vietnam where, in all evidence, it is endemic.